Implementation of Electronic Medical Records at Balong Community Health Center, Ponorogo Regency - Hapy Marsya Pradita; Dwi Nurjayanti (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2025)
Electronic Medical Records (EMR) are a form of digitalization in healthcare services aimed at improving efficiency, accuracy, and integration of patient data. This study aims to identify the implementation of EMR based on ideal implementation indicators at Puskesmas Balong, Ponorogo Regency. Data were obtained through observation and interviews with registration officers, medical staff, and the head of the health center using the EPUS Klaster application system. The results showed that EMR implementation had a positive impact by accelerating services, facilitating access to patient data, and improving coordination between units. However, obstacles such as network disruptions, lack of training, and dependency on third-party vendors remain significant. Managerial support was also found to be suboptimal in providing necessary facilities and infrastructure. It is necessary to strengthen human resource training, improve IT infrastructure, and conduct regular evaluations to ensure that EMR implementation runs optimally and sustainably.